2014
DOI: 10.1007/s11356-014-3918-0
|View full text |Cite
|
Sign up to set email alerts
|

Bivalve and barnacle larvae distribution driven by water temperature in a Mediterranean lagoon

Abstract: The objective of this study was to explore the relationships between the distribution of some meroplanktonic species and water temperature. Meroplankton larvae abundance of bivalves, and barnacles and water temperature fluctuations were studied from February 2011 to January 2012 at five stations in Ghar El Melh lagoon (GML) Mediterranean Sea, northern Tunisia). According to redundancy analysis (RDA), a significant difference was found in the distribution of larvae among the seasons (F = 10.28, p < 0.001); summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…Os organismos meroplanctônicos que ocorreram na praia do Goiabal, são encontrados em diversos ambientes costeiros (ZIADI et al, 2015). Foi observado que as larvas de poliqueta, se destacaram tanto em densidade quanto em riqueza e foram registradas em todos os meses amostrados.…”
Section: Discussionunclassified
“…Os organismos meroplanctônicos que ocorreram na praia do Goiabal, são encontrados em diversos ambientes costeiros (ZIADI et al, 2015). Foi observado que as larvas de poliqueta, se destacaram tanto em densidade quanto em riqueza e foram registradas em todos os meses amostrados.…”
Section: Discussionunclassified
“…Temperature is a major factor in the timing of the reproduction of barnacles and remains an important species-specific factor for spawning (Anil et al, 1995;Dattesh et al, 2006;Ziadi et al, 2015). The hatching peak of oysters often coincides with warmer water temperature, but barnacles often breed during relatively colder months and their larval peak is correlated to low temperature (Anil et al, 1995;Dattesh et al, 2006;Ziadi et al, 2015).…”
Section: Temporal Patterns Of Oyster and Barnacle Recruitmentmentioning
confidence: 99%
“…Temperature is a major factor in the timing of the reproduction of barnacles and remains an important species-specific factor for spawning (Anil et al, 1995;Dattesh et al, 2006;Ziadi et al, 2015). The hatching peak of oysters often coincides with warmer water temperature, but barnacles often breed during relatively colder months and their larval peak is correlated to low temperature (Anil et al, 1995;Dattesh et al, 2006;Ziadi et al, 2015). The present study indicated that the barnacle recruited earlier and longer (early spring to early winter) than the oyster (mid spring to late fall), with two distinct recruitment peaks (mid-spring and mid-summer) that were separate from those (August) of the oyster.…”
Section: Temporal Patterns Of Oyster and Barnacle Recruitmentmentioning
confidence: 99%